Impact of biomass fires on tropospheric nitrogen dioxide in South and Southeast Asia for the years from 2005 to 2014. (September 2017) - Yu, Bo; Chen, Fang; Shirazi, Zeeshan
Abstract: Nitrogen dioxide is a prominent air pollutant effecting public health, mainly formed by anthropogenic activities and biomass fires. To assess the impact of biomass fires on nitrogen dioxide, recent studies have analyzed the relationship between nitrogen dioxide and fires in relatively sparsely populated areas, avoiding the uncertainty of assessment caused by human activities. However, it is necessary to further investigate the relationship between nitrogen dioxide and fires in densely populated areas, which requires considering an appropriate way to distinguish between nitrogen dioxide from biomass fires and nitrogen dioxide from anthropogenic activities (e.g., industry). In this study, a new approach is proposed and applied to estimate the impact of biomass fires on tropospheric nitrogen dioxide in South and Southeast Asia, which has a high population density and is undergoing through the process of industrialization. We conducted ten year analysis of correlation (from 2005 to 2014) between nitrogen dioxide and fires, and further estimated the impacts of winter and summer monsoon on the correlation. The analysis indicates a high efficiency and reliability of this approach in presenting correlation between nitrogen dioxide and fire and demonstrates a strong monsoon impact on the correlation. Moreover, we concluded that the correlation is influenced by land use and local industrialization level as well. Graphical abstract: Highlights: Population density is applied for decreasing anthropogenic impact on the calculation of correlation between nitrogen dioxide and biomass fires. We analyze 10-year summer and winter monsoon impact on the correlation in South and Southeast Asia. Population density can be used to effectively decrease human impact. The correlation between nitrogen dioxide and fires over South and Southeast Asia is generally statistically strong, especially in flammable areas like forest.